2017
DOI: 10.1093/jxb/erx157
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis Cys2/His2 zinc finger transcription factor ZAT18 is a positive regulator of plant tolerance to drought stress

Abstract: ZAT18 modulated genes involved in hormone signaling transduction and stress response pathways, resulting in enhanced osmotic stress responses in seed germination and improved drought stress tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
79
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(87 citation statements)
references
References 55 publications
7
79
0
1
Order By: Relevance
“…ZATs appear to have a general role in mediating abiotic stress tolerance (e.g. cold, drought) (Yin et al, 2017), while ZAT14 integrates phosphate starvation responses (Devaiah et al, 2007). Interestingly, WRKY18 showed a clear cell type-specific pattern.…”
Section: Resultsmentioning
confidence: 99%
“…ZATs appear to have a general role in mediating abiotic stress tolerance (e.g. cold, drought) (Yin et al, 2017), while ZAT14 integrates phosphate starvation responses (Devaiah et al, 2007). Interestingly, WRKY18 showed a clear cell type-specific pattern.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, C2H2 ZFP is a eukaryotic transcription factor, which contains 1-4 zinc finger structures, and, in plants, it has a highly conserved QALGGH motif, which plays an important role in abiotic stress [23]. Since the first C2H2 ZFP gene EPF1 was isolated from petunia [24], more C2H2 ZFP family genes have been found in plants and widely reported to be involved in responses to biotic and abiotic stresses [25]. In Arabidopsis, constitutive expression of AtZAT7 or AtZAT10 improved salt tolerance [25,26].…”
mentioning
confidence: 99%
“…Since the first C2H2 ZFP gene EPF1 was isolated from petunia [24], more C2H2 ZFP family genes have been found in plants and widely reported to be involved in responses to biotic and abiotic stresses [25]. In Arabidopsis, constitutive expression of AtZAT7 or AtZAT10 improved salt tolerance [25,26]. Overexpression of ZAT18 enhanced drought tolerance of Arabidopsis [27], whereas AtZAT6 could regulate biotic and abiotic stress tolerance through the Salicylic Acid (SA) activation pathway [28].…”
mentioning
confidence: 99%
“…Overexpression of other ZFPs also results in an increase in tolerance to the stress that induces them. [7][8][9][10][11][12] Shi et al demonstrated that OEZat6 lines enhance tolerance to bacterial infection, freezing, drought and salinity stress, while artificial microRNA of Zat6 reduce tolerance. 11 Yin et al found that OEZat18 lines were more tolerant to drought stress while T-DNA mutant Zat18 lines were less tolerant.…”
mentioning
confidence: 99%
“…11 Yin et al found that OEZat18 lines were more tolerant to drought stress while T-DNA mutant Zat18 lines were less tolerant. 12 Only two ZFPs have been examined in potato. Tian et al characterized StZFP1 and found it to be induced by Phytophthora infestans, salinity and abscisic acid.…”
mentioning
confidence: 99%